Penerapan Unsur Tindak Pidana dengan Pemberatan Berdasarkan 363 Ayat (1) Ke-4 dan Ke-5 KUHP: Studi Kasus Putusan No. 65/Pid.B/2012/PN.Pwr - Halida, Reny; Sasongko, Dradjad Wahyu (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2024)
The recent rise in crime which is very disturbing to the public occurs all the time in the territory of the Republic of Indonesia. Mitigation and prevention efforts have been carried out, but until now there is still crime, the root causes of crime have not been optimally addressed. One form of crime that often occurs in society is theft. Seeing the current state of society, it is very possible for people to look for shortcuts by stealing. The mass media and electronic media show that the frequent occurrence of theft crimes of various types is motivated by inadequate living needs. As theft increases, other forms of theft also develop. That the correct application of articles based on the Criminal Code (KUHP), regarding aggravated theft, is that if all the elements of Article 363 paragraph (1) 4th and 5th, and so that they fall into the category of aggravated theft, then the perpetrator The theft must consist of more than two or more people and each must act as an author or participate in carrying it out as regulated in Article 55 of the Criminal Code, rather than one of the perpetrators only acting as an accessory as regulated in Article 56 of the Criminal Code.